Bulk message-passing model: metric space index a case of study - Gil Costa, Graciela Verónica (2008)
Synchronous and asynchronous approaches to model parallel programs are considered as two different schools. Intuition indicates that asynchronous programs should be more efficient since no periodical global time synchronization is required. However, in this paper we parallelize a resent index pivot-based technique for searching in metric spaces designed to improve bulk-massage-passing which reduce running times using a synchronous model. This model is designed to balance the load work en each machine between synchronizations and to reduce the number of synchronizations required to finish a batch of queries